Influenza B virus infections in Western Saxony, Germany in three consecutive seasons between 2015 and 2018: Analysis of molecular and clinical features. Issue 43 (8th October 2019) - Hönemann, M.; Martin, D.; Pietsch, C.; Maier, M.; Bergs, S.; Bieck, E.; Liebert, U.G.
Abstract: Background: The impact of annual influenza epidemics and prevailing strains varies worldwide and regional. The majority of vaccines used contained two influenza A strains and only one influenza B strain (trivalent vaccine). Aim: The aim of the study was to compare laboratory confirmed influenza B cases during three consecutive years with respect to vaccination history, clinical symptoms and molecular virology. Methods: Partial HA gene sequences were analyzed for lineage determination and complete HA sequence in cases with reported vaccination and in fatal cases. Clinical data were retrieved from patient charts. Findings: During the 2015/16 season, 75 influenza B cases were retrieved; 11 in 2016/17, and 274 in 2017/18. The frequency of Yamagata-lineage strains increased from 7.6% to 100%. No difference was detected in the relative frequency of co-morbidities in season 2017/18. 37.7% of the adult patients and 4.5% of pediatric patients were vaccinated against influenza. Interpretation: Phylogenetically, Yamagata strains clustered similarly in 2017/2018 when compared to the previous two influenza seasons. While the relative frequency of influenza B cases differed, the clinical symptoms remained similar. Conclusion: World Health Organization recommendations for the use of tetravalent vaccines that contain two influenza B strains (Yamagata and Victoria) in addition to the two influenza A strains (H1N1 and H3N2) should be implemented in national vaccination guidelines. Funding: This research was partially supported by the Association of Sponsors and Friends of Leipzig University.